Review Peningkatan Keandalan Sistem Kendali Pompa Submersible dengan Penambahan Phase Failure Relay di PT. Indofood Noodle Semarang - Ahmad Faidlon (International Forum of Researchers and Lecturers, 2023)
This research addresses water supply issues at PT. Indofood CBP Sukses Makmur Semarang, Noodle Division. The Submersible Pump often experiences damage, such as Short Circuits due to phase failure. To address this, a Phase Failure Relay (PFR) was added to control the pump. The study employs observation, literature review, and interviews to evaluate the impact of PFR on pump control and safety aspects. The research findings indicate that the addition of PFR successfully prevents damage, with the potential for reducing repair costs, providing a practical solution in controlling the Submersible Pump at PT. Indofood.